Chronic allograft rejection: a fresh look. Issue 1 (February 2015) - Wedel, Johannes; Bruneau, Sarah; Kochupurakkal, Nora; Boneschansker, Leo; Briscoe, David M.
Abstract : Purpose of review: New developments suggest that the graft itself and molecules expressed within the graft microenvironment dictate the phenotype and evolution of chronic rejection. Recent findings: Once ischemia-reperfusion injury, cellular and humoral immune responses target the microvasculature, the associated local tissue hypoxia results in hypoxia-inducible factor 1α-dependent expression of pro-inflammatory and proangiogenic growth factors including vascular endothelial growth factor (VEGF) as a physiological response to injury. Local expression of VEGF can promote the recruitment of alloimune T cells into the graft. mTOR/Akt signaling within endothelial cells regulates cytokine- and alloantibody-induced activation and proliferation and their proinflammatory phenotype. Inhibition of mTOR and/or Akt results in an anti-inflammatory phenotype and enables the expression of coinhibitory molecules that limit local T cell reactivation and promotes immunoregulation. Semaphorin family molecules may bind to neuropilin-1 on regulatory T cell subsets to stabilize functional responses. Ligation of neuropilin-1 on Tregs also inhibits Akt-induced responses suggesting common theme for enhancing local immunoregulation and long-term graft survival. Summary: Events within the graft initiated by mTOR/Akt-induced signaling promote the development of chronic rejection. Semaphorin–neuropilin biology represents a novel avenue for targeting this biology and warrants further investigation.